THE PRIMARY EFFECTS OF SOCIAL MEDIA AND SOCIAL CAPITAL ON GREEN BUYING BEHAVIOUR: A THEORETICAL REVIEW - Jingyang, Liu; May, Amy Yeo-Chu; Teng, Phuah Kit (International Journal of Application on Economics and Business, 2024)
The increasing significance of the link between millennials' social media use and their social capital is the focus of this paper. The objective is to provide a well-organized framework for grasping this connection, emphasizing the primary factors that affect environmentally conscious consumer behaviour. To accomplish this, the authors conducted an initial examination of secondary data from various sources, including library databases like Emerald, Science Direct, Scopus, Clarivate-WOS and EBSCOhost, as well as external sources such as Google Scholars. By meticulously applying 4-step selection criteria during the screening process, the authors structured and consolidated relevant concepts and terms associated with social capital, social media use, and green perceived buying behaviour (GPBB). The systematic review revealed intriguing discoveries, particularly in relation to GPBB in China, which suggests new research avenues in this field. The study also outlines potential directions for future research, providing valuable insights for scholars interested in understanding the factors that influence GPBB. This framework, as presented in this research, not only aids academics and practitioners in comprehending GPBH but also assists marketers in managing customer relationships and achieving sales goals. This exploratory data analysis marks the initial phase of establishing a well-structured framework for comprehending GPBB and its primary influencers, with the possibility of further research paradigms to yield more conclusive results.